Graphs and lattices as conceptual representation formats. An exploratory exercise with five specializations of Mendelian genetics - Casanueva, Mario (2012)
Fil: Casanueva, Mario. Universidad Autónoma Metropolitana. Unidad Cuajimalpa. Departamento de Humanidades; México.